2017
DOI: 10.1186/s11671-017-1984-1
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Flow and Heat Transfer Characteristics of Ethanol/Polyalphaolefin Nanoemulsion Flowing Through Circular Minichannels

Abstract: This work experimentally studied the convective flow and heat transfer characteristics of a novel nanostructured heat transfer fluid: “ethanol/polyalphaolefin nanoemulsion” flowing through 12 circular minichannels of 1-mm diameter each. Ethanol/polyalphaolefin nanoemulsion is a thermodynamically stable system formed by dispersing ethanol into a mixture of “polyalphaolefin (PAO)” and surfactants. In this study, ethanol/PAO nanoemulsion is used as the working fluid to study the effect of ethanol nanodroplets on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…5 that for tube diameters below 1 mm, the flow boiling was mostly in the laminar region. Trinh and Xu [85] specified in their experimental study of ethanol/polyalphaolefin nanoemulsion flowing through circular minichannels that the ethanol nano-droplets formed through the nano-emulsion process could significantly enhance the HTC compared to the base fluid. It was suggested that the phase change process of ethanol nano-droplets under flow boiling condition absorbed a relatively large amount of latent heat, which could be one of the reasons for the heat transfer enhancement.…”
Section: Effects Of Reynolds Number and Flow Regimes On Flow Boiling Of Binary Mixturesmentioning
confidence: 99%
“…5 that for tube diameters below 1 mm, the flow boiling was mostly in the laminar region. Trinh and Xu [85] specified in their experimental study of ethanol/polyalphaolefin nanoemulsion flowing through circular minichannels that the ethanol nano-droplets formed through the nano-emulsion process could significantly enhance the HTC compared to the base fluid. It was suggested that the phase change process of ethanol nano-droplets under flow boiling condition absorbed a relatively large amount of latent heat, which could be one of the reasons for the heat transfer enhancement.…”
Section: Effects Of Reynolds Number and Flow Regimes On Flow Boiling Of Binary Mixturesmentioning
confidence: 99%
“…Recently, the authors have proposed a new type of heat transfer fluid called "nanoemulsion" [47]. Nanoemulsion is a suspension of liquid nanodroplets formed by self-assembly inside another immiscible fluid, as part of a broad class of multiphase colloidal dispersions [48].…”
Section: Ethanol/polyalphaolefin Nanoemulsion: a Novel Heat Transfer mentioning
confidence: 99%
“…The droplets typically have a length scale less or equal to 50 nm, which makes the nanoemulsion fluid thermodynamically stable and transparent to natural light. A comparison of nanoemulsion with emulsion (dilute emulsion) is represented in Table 3 [47,48]. Table 3.…”
Section: Ethanol/polyalphaolefin Nanoemulsion: a Novel Heat Transfer mentioning
confidence: 99%
“…Although many experimental studies have been conducted to date to investigate the impact of local vapor quality on boiling heat transfer performance, majority of these studies have taken the similar approach to measure local vapor quality Experimental Approaches to Measurement of Vapor Quality of Two-Phase Flow Boiling DOI: http://dx.doi.org /10.5772/intechopen.94473 only at the outlet of test section mainly under uniform wall heat flux boundary conditions using electrical heating [6][7][8][9][10][11][12]. There are limited studies investigating the effect of local vapor quality for other thermal boundary conditions [13,14], while their techniques to measure local vapor quality are not reported clearly.…”
Section: Introductionmentioning
confidence: 99%